Preliminary assessment of the performance of freshman students in engineering algebra at DLSU-Manila - Baraoidan, Wilheliza A. (Animo Repository, 2006)
This preliminary study aims to assess the performance of freshman students in Engineering Algebra or ENGALGE, a core mathematics subject for engineering students of DLSU-Manila. In this course, the computational laboratory requires the students to solve exercises in the classroom during regular periods immediately after which they are given feedback on their performance. The study was done by giving the students the pre-test and post-test on the first day of classes and during the final examinations, respectively. The scores were analyzed using the paired t-test for means and t-test for unequal variances. Results showed a significant increase in the scores from the pre-test to the post-test at 99% confidence level.